111k views
1 vote
Multiply factor 8(x-3y)(x+3y) to determine the original polynomial

User Msc
by
5.9k points

2 Answers

5 votes
let a = 8(x - 3y)(x + 3y)

by multiplying the functions in the bracket first
⇒ a = 8[ x² + 3xy - 3xy - 9y²]
a = 8 [x² - 9y²]

by now expanding the brackets
⇒ a = 8x² - 72y²
User Daedalus
by
6.4k points
3 votes
If I'm doing this correctly, you would need to multiply everything inside the parenthesis by 8. So it would be 8x-24y·8x+24y. I'm sorry if that's not right, but that is my interpretation of the problem. Hope I was of some assistance :)
User Topr
by
5.8k points